Investigation of the Ferredoxin’s Influence on the Anaerobic and Aerobic, Enzymatic H2 Production - Koo, Jamin; Cha, Yeeun (Frontiers in Bioengineering and Biotechnology, 2021)
Ferredoxins are metalloproteins that deliver electrons to several redox partners, including [FeFe] hydrogenases that are potentially a component of biological H2 production technologies. Reduced ferredoxins can also lose electrons to molecular oxygen, which may lower the availability of electrons for cellular or synthetic reactions. Ferredoxins thus play a key role in diverse kinds of redox biochemistry, especially the enzymatic H2 production catalyzed by [FeFe] hydrogenases. We investigated how the yield of anaerobic and aerobic H2 production vary among the four different types of ferredoxins that are used to deliver electrons extracted from NADPH within the synthetic, fermentative pathway. We also assessed the electron loss due to O2 reduction by reduced ferredoxins within the pathway, for which the difference was as high as 5-fold. Our findings provide valuable insights for further improving biological H2 production technologies and can also facilitate elucidation of mechanisms governing interactions between Fe-S cluster(s) and molecular oxygen.